Perubahan Komposisi Mikrob dalam Proses Fermentasi Kopi Honey dan Natural - Kamaluddin, Nadia Nuraniya; Solihin, Eso; Suryatmana, Pujawati; Januar, Dodi Ganjar; Rainaldi, Rainaldi; Setiawan, Ade (Soilrens, 2023)
This study investigates the microbial populations during different coffee fermentation processes and their impact on coffee quality. Bacillus, Pseudomonas, and endophytic populations in coffee beans undergoing natural saccharic and natural lactic fermentation remained unchanged compared to fresh coffee beans. However, a notable increase in Bacillus population occurred in honey saccharic fermentation, possibly attributed to the high sugar content in the mucilage, supporting bacterial growth. Additionally, the introduction of Lactobacillus and Saccharomyces during fermentation enhanced sugar consumption and influenced the final coffee quality, particularly aroma profile and nutritional composition. Varietal differences were observed, with Bacillus population decreasing slightly post-fermentation, especially in honey saccharic and natural lactic processes. This decline may be attributed to the dominance of Saccharomyces and Lactobacillus, antagonistic to Bacillus, and the fermentation conditions leading to decreased pH, unfavorable for Bacillus. These findings highlight the intricate microbial interactions and their implications for coffee fermentation and quality.